Building rich web applications with Ajax - Paulson, L.D. (Computer (Long Beach, Calif.), 2005)
Looks at how developers are going back to the future by building Web applications using Ajax (Asynchronous JavaScript and XML), a set of technologies mostly developed in the 1990s. A key advantage of Ajax applications is that they look and act more like desktop applications. Proponents argue that Ajax applications perform better than traditional Web programs. As an example, Ajax applications can add or retrieve new data for a page it is working with and the page will update immediately without reloading.